Brief Underage Alcohol Use Screener Scores Predict Health Risk Behaviors. (October 2021) - Tubman, Jonathan G.; Meca, Alan; Schwartz, Seth J.; Velazquez, Maria Rosa; Egbert, Andrew W.; Soares, Mary H.; Regan, Timothy
The aim of this study was to determine if adolescents' scores on a 2-item underage alcohol use screener predict risky consequences of past-year alcohol use and other health risk behaviors in a nonclinical, school-based sample of adolescents. A predominantly minority sample of 756 middle and high school students completed in-school tablet-based surveys on past-year underage alcohol use and a range of health risk behaviors. Higher scores for self alcohol risk and peer alcohol risk were associated with higher risk of past-year riding with a drunk driver and past 90-day measures of cigarette use, marijuana use, unplanned sex, and unprotected intercourse. The National Institute of Alcohol Abuse and Alcoholism Brief Alcohol Screener is a useful tool for school-based service providers, including school nurses, to identify and address the needs of adolescents at high risk of the development of alcohol use disorders, as well as a range of preventable health risk behaviors.